PENGARUH METODE MIND MAP TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN GUGUS 4 SELAPARANG - Fitriani, Nurul Amalia; Nurhasanah, Nurhasanah (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2018)
This research aims to find out the description of the application of the Mind Map method in class V social studies learning, whether there is an influence of the Mind Map method on the social studies learning outcomes of class V students at SDN Gugus 4 Selaparang. This research uses a quantitative experimental method, Quasi Experimental type Nonequivalent Control Group Design. The population in this study were fifth grade elementary school students in cluster 4 in Selaparang District, namely SDN 33 Mataram, SDN 34 Mataram, SDN 24 Mataram and SDN 10 Mataram. The samples were SDN 33 Mataram as the experimental class and SDN 34 Mataram as the control class. The sampling technique used was Nonprobability Sampling with a Purposive Sampling technique. Data collection was carried out using objective test methods to obtain learning outcome data and documentation methods to obtain data in the form of photos of student and teacher activities during the learning process. Learning outcomes data were analyzed using the polled variance t-test. Before testing the hypothesis, the data obtained is first tested for normality and homogeneity of the data. After carrying out the analysis, the tcount result was 2.601, while the ttable was 2.001 at a significance level of 5%, which means that there was an influence of the Mind Map Method on the Social Studies Learning Outcomes of Class V Students at SDN Gugus 4 Selaparang.